The Phantom Menace of Omitted Variables – A Comment - Nolan Ritter; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
This note demonstrates that in applied regression analysis, the variance of a coefficient of interest may decrease from the inclusion of a control variable, contrasting with Clarke's assertion (2005, 2009) that the variance can only increase or stay the same. Practitioners may thus be well-advised to include a relevant control variable on this basis alone, particularly when it is weakly correlated with the variable of interest. – – Das vorliegende Papier zeigt, dass das Hinzufügen einer zusätzlichen Kontrollvariablen in eine Regressionsanalyse die Varianz des interessierenden Koeffizienten senken kann, was der Darstellung von Clark (2005, 2009) widerspricht. Daher wird geraten, theoretisch begründete Kontrollvariablen aufzunehmen, insbesondere wenn diese mit der Variablen von Interesse schwach korreliert sind.
Keywords: C12; C15; C18; 330; Control variables; variance; model specification; Control variables; variance; model specification